Implementasi Sistem Boarding School dalam Membentuk Kepribadian Siswa pada Yayasan Pendidikan Islam Matholi’ul Huda Troso (Madrasah Aliyah dan Madrasah Tsanawiyah) - Savitri, Dewi; Laila, Azzah Nor (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Boarding school is an effective educational environment to instill character education for students. The boarding school system at YPI Matholi'ul Huda Troso is quite conducive for students and/or santri to focus on their education. Therefore, this study analyzes the implementation of the Boarding school system in shaping students' personalities at YPI Matholi'ul Huda Troso. This research uses a qualitative approach with a case study method. Data collection techniques are in the form of interviews with teachers, ustadzh/ustdzah, and students and/or santri as well as observation to see the daily activities of the YPI Matholi'ul Huda Troso boarding school environment. The results of this study indicate that implementation of the Boarding school system in shaping students' personalities at YPI Matholi'ul Huda Troso shws positive results in shaping student’s personalities such as discipline, independence, responsibility, social interaction, faith, and leadership show significant improvment. By integrating academic and non academic life in one controlled environment, this system ensures that every aspect of student life is aligned with the vision and mission of the madrasah. Thus, learning character values is not only at the cognitive level, but also touches on internalization and real practice in daily life.